Ultrathin and Flexible CNTs/MXene/Cellulose Nanofibrils Composite Paper for Electromagnetic Interference Shielding - Cao, Wentao; Ma, Chang; Tan, Shuo; Ma, Mingguo; Wan, Pengbo; Chen, Feng (Nano-Micro Letters, 2019)
As the rapid development of portable and wearable devices, different electromagnetic interference (EMI) shielding materials with high efficiency have been desired to eliminate the resulting radiation pollution. However, limited EMI shielding materials are successfully used in practical applications, due to the heavy thickness and absence of sufficient strength or flexibility. Herein, an ultrathin and flexible carbon nanotubes/MXene/cellulose nanofibrils composite paper with gradient and sandwich structure is constructed for EMI shielding application via a facile alternating vacuum-assisted filtration process. The composite paper exhibits outstanding mechanical properties with a tensile strength of 97.9 ± 5.0 MPa and a fracture strain of 4.6 ± 0.2%. Particularly, the paper shows a high electrical conductivity of 2506.6 S m−1 and EMI shielding effectiveness (EMI SE) of 38.4 dB due to the sandwich structure in improving EMI SE, and the gradient structure on regulating the contributions from reflection and absorption. This strategy is of great significance in fabricating ultrathin and flexible composite paper for highly efficient EMI shielding performance and in broadening the practical applications of MXene-based composite materials. Highlights: 1 An ultrathin and flexible carbon nanotubes/MXene/cellulose nanofibrils composite paper with gradient and sandwich structure was successfully fabricated via a facile alternating vacuum-assisted filtration process. 2 The composite paper exhibits excellent mechanical property and electromagnetic interference shielding performance.